2021
DOI: 10.2490/prm.20210034
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural Adaptation of the Health Sciences Evidence-based Practice Questionnaire into Japanese and Its Test–Retest Reliability in Undergraduate Students

Abstract: The Health Sciences Evidence-Based Practice (HS-EBP) questionnaire was recently developed for measuring five constructs of evidence-based clinical practice among Spanish health professionals by applying content and construct validity investigation. The current study aims to undertake a cross-cultural adaptation of the HS-EBP into Japanese and to investigate the internal consistency and test-retest reliability of the Japanese HS-EBP among undergraduate students of nursing and physical and occupational therapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Data were collected through a name-based online survey (SurveyMonkey). In accordance with the previous study, 13 ) the participants rated each question, including the explanatory text, on a five-point numerical rating scale (1: the meaning is not understood at all as Japanese; 5: the meaning is fully understood as Japanese). The participants were asked to comment freely on what part of the expression was unclear or how it should be corrected when they chose ratings 1–3.…”
Section: Methodsmentioning
confidence: 82%
“…Data were collected through a name-based online survey (SurveyMonkey). In accordance with the previous study, 13 ) the participants rated each question, including the explanatory text, on a five-point numerical rating scale (1: the meaning is not understood at all as Japanese; 5: the meaning is fully understood as Japanese). The participants were asked to comment freely on what part of the expression was unclear or how it should be corrected when they chose ratings 1–3.…”
Section: Methodsmentioning
confidence: 82%
“…This study found that the final academic degree was a statistically significant contributing factor for s-SAPCPTS scores, but the effect size of R 2 = 0.09 can be interpreted as a none-to-very weak effect size [ 29 ]. These findings indicate that other factors that are relevant to the final academic degree may better influence the s-SAPCPTS scores, for example, pain neurophysiology knowledge [ 30 , 31 ] and adherence to evidence-based practice [ 16 , 32 ]. Further, skills for behavioral modifications, which can be enhanced in post-graduate clinical training, for example, skills to enhance patient’s attitude toward self-management [ 33 ] and communication skills to enhance patient autonomy [ 34 ], may better influence the s-SAPCPTS scores than the academic degree.…”
Section: Discussionmentioning
confidence: 99%
“…As dependent variables, the Japanese HS-EBP 10 ) , a reliable and validated five-dimensional questionnaire on EBP 8 , 9 , 10 ) , was used. Dimension 1 focuses on beliefs and attitudes and includes 12 items (e.g., “I consider EBP improves the quality and results of interventions”).…”
Section: Participants and Methodsmentioning
confidence: 99%
“…There was no comprehensive measure to evaluate EBP attitudes and implementation until recently, so only ambiguous relationships between research activities and EBP attitudes and behaviors could be verified, as in the study by Fujimoto et al 2 ) . Recently, a multidimensional questionnaire called health sciences evidence-based practice (HS-EBP) 8 , 9 , 10 ) was developed to comprehensively assess attitudes and implementation of EBP, and normative scores were known in Spain 11 ) . Under such circumstance, the purpose of this study was to determine which research activities influence rehabilitation professionals’ attitudes and implementation of EBP.…”
Section: Introductionmentioning
confidence: 99%